2021
DOI: 10.1016/j.heliyon.2021.e07667
|View full text |Cite|
|
Sign up to set email alerts
|

Organochlorine pesticide residues in tea and their potential risks to consumers in Ethiopia

Abstract: Tea is the most frequently consumed drink in the sphere; next to the water. However, tea can be contaminated by different pesticides particularly those outdated pesticides which have been familiar as one of the main difficulties in Ethiopia and contaminate the food commodities. From a study done in south west of Ethiopia, Dichlorodiphenyltrichloroethane (DDT) and endosulfan were detected in commonly consumed food items. Therefore, the main aim of this study was to analyze the residue of organochlorine pesticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This may reduce the applicability of analytical method in some situations. From Table 4 , very high LOD and LOQ (60–720 ng/g and 30–2400 ng/g) were observed from tea [ 269 ], (10–100 ng/mL and 100–10000 ng/mL) [ 69 ], (12–987 ng/g and 40–3290 ng/g) from fruits and vegetables [ 270 ], and (3700–4800 and 12–16000 ng/mL) [ 271 ], (180–780 ng/g and 62–2380 ng/g) [ 272 ] from human milk ( Table 5 ), respectively. Similarly, Serum of a leopard also showed high LOD (800–34000 ng/mL) [ 25 ], (150–12730 ng/mL) [ 273 ], ( Table 5 ).…”
Section: Results and Discussion: Literature Reviewmentioning
confidence: 99%
“…This may reduce the applicability of analytical method in some situations. From Table 4 , very high LOD and LOQ (60–720 ng/g and 30–2400 ng/g) were observed from tea [ 269 ], (10–100 ng/mL and 100–10000 ng/mL) [ 69 ], (12–987 ng/g and 40–3290 ng/g) from fruits and vegetables [ 270 ], and (3700–4800 and 12–16000 ng/mL) [ 271 ], (180–780 ng/g and 62–2380 ng/g) [ 272 ] from human milk ( Table 5 ), respectively. Similarly, Serum of a leopard also showed high LOD (800–34000 ng/mL) [ 25 ], (150–12730 ng/mL) [ 273 ], ( Table 5 ).…”
Section: Results and Discussion: Literature Reviewmentioning
confidence: 99%
“…In another similar study in China, specifically on tea marketed in the Tehran market, their results revealed that consumed tea in Iran is free of pesticide residues or has residues that are lower than existing MRLs [4] , [45] . Natural factors such as temperature, rainfall, volatilization, photolysis, ventilation, biodegradation, pH, dew, and growth dilution, as well as the pre-harvest period between the last application and harvesting, can cause pesticide residues in tea bushes to degrade [39] , [32] , [44] , [40] . In South Africa, the demand for organic farming has increased as customers become more health conscious and the role of food in maintaining a healthy lifestyle, which has contributed to the low use of chemicals in agriculture [43] .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the risk assessment of 42 pesticides in Tieguanyin tea showed that long-term use of Tieguanyin tea does not pose serious health risks (Yao et al, 2022). Siraj et al (2021) investigated OCPs in different brands of tea in the Ethiopian market and their potential risks to consumers. From the detected pesticides, the average concentration of DDT (0.292-0.825 mg/kg) was higher than the MRL established by China (0.2 mg/kg), and the EDI of γ-chlordane and endrin was higher than the ADI, suggesting a potential health risk to consumers from the long-term consumption of tested tea leaves.…”
Section: Risk Assessmentmentioning
confidence: 99%